In search of better lives: analyzing post-soviet migration from Tajikistan to Russia - Davlyatova, Nodira (Kansas State University, 2014)
With the collapse of the socialist model in the former Union of Soviet Socialist Republics (USSR) in 1991 which was followed by Civil War (1992-1997), Tajikistan has undergone profound social, economic, and political transformation. Persistent impoverishment, political and economic instability, and discrimination of ethnic minorities have resulted in out-migration of Tajik population to Russia. In this study, labor migration (survival driven, seasonal, and chain) is discussed. Even though Tajik migrants face challenges such as segregation, xenophobia, sexism, and intolerance working abroad, they continue to migrate to Russia in order to seek a better quality of life. This is closely linked to migration policy and regulations that have been implemented by the governments of these countries which allow free movement across the borders. Although these migration policies promote legal migration, they create favorable conditions for inequality (such as structural, social, and global) as well as illegal migratory flows. However, little scholarly work has been focused on how migration policy contributes to structural inequality and leads to illegal migration in the former Soviet Republics. In my study, I seek to add to the limited existing literature about these phenomena. I examine the social context of Tajik labor migration, legal framework, migration policy and regulations, and its implications. Specifically, I analyze the case of Tajikistan and Russia’s migration policies and regulations as they are proposed and implemented by governmental agencies in collaboration and consultation with civil society organizations (local and international) including the Tajik diasporas.
Keywords: Migration; Policy; Tajikistan; Russia; Post-Soviet studies; Migration management; Sociology (0626)